THE RICHNESS OF REASONS TO IMPROVISE : Finding balance between the technical and artistic aspects in the practice and pedagogy of vocal group improvisation - Rajala, Merja (Merzi) (Taideyliopiston Sibelius-Akatemia, 2018)
Finding balance between the technical and artistic aspects in the practice and pedagogy of vocal group improvisation. In this master´s project, I wanted to deepen my understanding of the techniques, tools and know-how in vocal improvising and then see if I could get past the technical emphasis often placed in the teaching of vocal improvisation. I chose improvisational aspects with different qualities, hoping to be able to use them as a "richness of reasons to improvise" both in my artistic and pedagogical work. The central objective of this master´s project is to use research to discover new artistic and pedagogical tools to collective vocal improvisation with groups with different backgrounds. The final project is comprised of two parts: 1. A one hour improvised final concert, Waiting to hear it (Helsinki Music Centre, May 2018) showcasing the artistic outcomes of this research. The final concert is guided by these sub questions: - How can I present collective vocal improvisation in a way that satisfies me artistically? - How can the pedagogical outcomes and the values of the process be expressed artistically on the stage? - How can I use improvisation methods to facilitate collective composition processes presented in the concert? 2. This reflective text in which I present the project and summarise my pedagogical and artistic growth in the process. As such, this text is guided by the followong sub questions: - How does my understanding of teaching choral improvisation expand through the process of applying a variety of improvisation methods and tools in various choral settings? - How can applying a variety of improvisation methods and tools in different choral settings help me to find balance between technical and artistic aspects of improvisation in my teaching and artistic practise? - What additional skills can be taught through choral improvisation? Writing this refelctive text was done in parallel with planning the concert.
Keywords: co-creation; inventing music; Vocal Painting; Circle Singing; status behaviour; collaborative research process; contact improvisation; connection; choral improvisation; choral music; improvisation; Global Music